Moving spaces with Anna Bella Geiger - Laurentiis, Gabriela de (Farol, 2024)
The essay approaches modes of creation by Anna Bella Geiger (Rio de Janeiro, 1933), focusing on problems related to the production of spaces in expanded senses. I present how Geiger articulates a critique of the modes of production of bodies and territories, highlighting her place of action, as an artist working in the Global South. In her passages between modern and contemporary artistic practices, Anna Bella Geiger makes works in conversation with an accurate critique of the stagnant models of femininity, through which women are, historically, removed from the imaginary of artistic creation. Likewise, they problematize spatialities in multiple layers, tensioning binary polarities, such as public/private, superior/inferior.